Informal irrigated vegetable value chains in urban Ghana: potential to improve food safety through changing stakeholder practices - Galibourg, David; Amankwaa, E. F.; Gough, K. V.; Scott, R. (Liverpool University Press, 2024)
Contaminated vegetables grown and consumed in cities of the global South have adverse public health consequences. Through interviews with farmers, traders, consumers and institutional representatives, this article explores why stakeholders in the irrigated vegetable value chain in Accra continue unsafe practices. The multi-stakeholder data are analysed by combining a behavioural model with a framework of complex stakeholder interactions. Arguably, a systemic approach would help meet stakeholders’ opportunity, capability and motivation needs and actualise current efforts to promote safe practices. Findings indicate the need for all stakeholders to develop a shared understanding of each other’s practices and co-design flexible arrangements that better integrate their diverse rationales, knowledge and constraints. Improving hygiene and food safety from farm to fork requires political commitment that accounts for land tenure insecurity and the high cost of safe water.